1998
DOI: 10.3168/jds.s0022-0302(98)75806-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Health Disorders, and Relationships with 305-Day Milk Yield and Conformation Traits of Registered Holstein Cows

Abstract: A total of 4368 first lactation records for Holstein cows from 30 herds was used to estimate genetic parameters for yield, conformation traits, and the binary coded disease traits of udder edema, milk fever, retained placenta, metritis, displaced abomasum, ketosis, cystic ovary, mastitis, and lameness. Data on health, parentage, and yield came from an on-farm program for record keeping and management. Test day production data were obtained from British Columbia DHI. Type classification data were received from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
76
8
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 23 publications
33
76
8
9
Order By: Relevance
“…Most estimates of heritability were higher than 0.17 ( Figure 1) and resemble the results observed in the literature for Holstein herds in countries like Australia, USA and Canada (Thompson et al, 1983;Misztal et al, 1992;Van Dorp et al, 1998).…”
Section: Resultssupporting
confidence: 74%
“…Most estimates of heritability were higher than 0.17 ( Figure 1) and resemble the results observed in the literature for Holstein herds in countries like Australia, USA and Canada (Thompson et al, 1983;Misztal et al, 1992;Van Dorp et al, 1998).…”
Section: Resultssupporting
confidence: 74%
“…Genetic correlations between these traits (not shown) were not statistically different from zero (P > 0.05). A positive genetic correlation between milk yield and lameness is reported in the literature (Van Dorp et al, 1998;Koenig et al, 2005;Buch et al, 2011). Our results suggest that phenotypic correlations in Figure 6 mainly illustrate an unfavourable environmental correlation; lame cows have lower feed intake and consequently, lower milk yield.…”
Section: Resultssupporting
confidence: 71%
“…On the other hand, the quadratic relationships of rear leg side view, which is also an intermediate optimum trait, were not statistically significant from zero (P > 0.05); instead, the linear ones were, suggesting that straight rear legs are associated with improved locomotion and less lameness. Van Dorp et al (1998 and reached the same conclusion. Furthermore, it has been suggested that such conformation is also associated with a longer productive life (Holstein Association USA, 2012).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, Kadarmideen (2004) obtained an estimate of 0.13 for the genetic correlation between milk and SCS, which is close to this study (0.12). Genetic correlations between milk and lameness were also within the range reported by other studies (0.13 to 0.48; Pryce et al, 1997 and1998;Van Dorp et al, 1998). A high milk yield is predisposing to mastitis or lameness, although a case of either of these will decrease the yields for the remainder of the lactation (Hagnestam et al, 2007) and particularly mastitis will affect milk yields of subsequent lactations because of impaired or destroyed secretory tissues of the udder (Lucey and Rowlands, 1984).…”
Section: Genetic Correlationssupporting
confidence: 80%